An improved MAC Protocol with reconfiguration scheme for Wireless e-Health Systems requiring quality of service - Gama, Oscar (2009)
To provide a reliable assistance to patients, emergency and intensive care systems have increased demands for quality of service at different levels, including at the MAC layer. The Low Power Real Time (LPRT) MAC protocol presents suitable characteristics to address these demands due to its efficient bandwidth allocation, low energy consumption, and bounded latency. Yet, this MAC protocol may still present a significant packet loss ratio in a wireless channel affected by errors. In order to improve its robustness to bit error conditions, a solution based on short size beacons is proposed and tested. Results show that significant improvements regarding packet loss ratio and energy saving are obtained. A new reconfiguration scheme is also proposed so that a WSN using this solution may react optimally in accordance with the patients' clinical state.